2013
DOI: 10.1016/j.foreco.2013.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire survival and regeneration of Eucalyptus globulus in forest plantations in Portugal

Abstract: Eucalyptus globulus is one of the most important pulpwood plantation species in the world, and nowadays it is present in most continents. Some of the regions where E. globulus plantations have been expanding have a high incidence of wildfires; therefore, knowing the factors affecting the fire resistance and resilience of this species is particularly important for forest management. This is the case of Portugal, where nearly 1.4 million ha of land burned in the last decade and where E. globulus has become the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 79 publications
(109 reference statements)
2
32
0
Order By: Relevance
“…The post-fire mortality models developed indicate that the conifers are the most prone to suffer mortality after wildfire, whereas the broadleaves are more resistant to fire ( Figure 5). This confirms the generally low fire susceptibility observed in most broadleaved trees compared with other forest types, probably explained by differences in fuel load composition, moisture content, flammability, and broadleaves resprouting ability (e.g., [3,34,35,70,71]). Previous studies argued that the conifers have higher flammability because their contents in resins and oils [32,70].…”
Section: Forest Composition Heterogeneity and Structuresupporting
confidence: 68%
See 1 more Smart Citation
“…The post-fire mortality models developed indicate that the conifers are the most prone to suffer mortality after wildfire, whereas the broadleaves are more resistant to fire ( Figure 5). This confirms the generally low fire susceptibility observed in most broadleaved trees compared with other forest types, probably explained by differences in fuel load composition, moisture content, flammability, and broadleaves resprouting ability (e.g., [3,34,35,70,71]). Previous studies argued that the conifers have higher flammability because their contents in resins and oils [32,70].…”
Section: Forest Composition Heterogeneity and Structuresupporting
confidence: 68%
“…In the literature we can find two main types of models, the ones based on variables reflecting fire injury indicators and those based on biometric information. Here, while the proposed approach employs some concepts that featured in earlier work (e.g., [17,18]) on the whole, the selected post-fire mortality models tend to differ significantly from other well-known classic approaches for fire-induced mortality (e.g., [34,35,69]). However, the use of the latter methods in long-term forest management planning is constrained by the difficulty to predict accurately the fire injury/severity variables they use (e.g., crown-kill, bole-kill or fire intensity are information rarely available to forest beforehand).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown an average of ten shoots for each Tapirira guianensis tree (Jancosky 2010) and some Eucalyptus species can produce up to 21 basal resprouts (Catry et al 2013). For aerial resprouts some interesting differences appeared: individuals of Guapira and Dalbergia were not fully covered with new leaves and branches, and some had not flushed at all, after one entire post-burning growing season, surviving predominantly by basal resprouts, while Eriotheca intensively invested PCH=Percentage of tree charred height, BR=number of basal resprouts and AR=intensity of aerial resprouts, s: soon after fire.…”
Section: Discussionmentioning
confidence: 95%
“…We assessed one commonly used indicator of fire severity and potential tree injury: the proportion of Acta Botanica Brasilica -30(4): 693-699. October-December 2016 tree charred height (PCH: Catry et al 2013). …”
Section: Sampling Designmentioning
confidence: 99%
“…Eucalyptus globulus is one of the most commercially important hardwood species. In 2004, there were about 2.5 million hectares planted worldwide (Catry et al, 2013). Eucalyptus production and processing generates a large amount of wood residues, such as sawmill residues or bark and branches currently left in the field.…”
Section: Introductionmentioning
confidence: 99%